Extension of Goosander Mergus merganser distribution into the Carpathian Mountain range - Kajtoch, Åukasz; Bobrek, RafaÅ‚ (Wildfowl, 2014)
The Goosander Mergus merganser occurs mainly in the Holoarctic boreal zone but isolated populations also exist in the Alps, the Balkans and in central Asia. In the lateÂ 20th century, the breeding distribution extended to the Carpathian Basin in centralÂ Europe, and the species is now widespread in the west of the Carpathian MountainÂ range, whilst remaining scarce in the east Carpathians and breeding only occasionallyÂ in the southern Carpathians. It was estimated that at least 240â€“360 pairs bred in theÂ Carpathian Mountains in 2010â€“2013 (of which c. 80% were in Poland), where they areÂ restricted to river valley systems which are generally in a natural or semi-natural state.Â This remains a rare species in central Europe, meriting conservation measures in theÂ Carpathians and monitoring of its continued expansion in the region.